Host-Derived Leukotriene B4 Is Critical for Resistance against Invasive Pulmonary Aspergillosis - Caffrey-Carr, Alayna K.; Hilmer, Kimberly M.; Kowalski, Caitlin H.; Shepardson, Kelly M.; Temple, Rachel M.; Cramer, Robert A.; Obar, Joshua J. (Frontiers in Immunology, 2018)
Aspergillus fumigatus is a mold that causes severe pulmonary infections. Our knowledge of how immune competent hosts maintain control of fungal infections while constantly being exposed to fungi is rapidly emerging. It is known that timely neutrophil recruitment to and activation in the lungs is critical to the host defense against development of invasive pulmonary aspergillosis, but the inflammatory sequelae necessary remains to be fully defined. Here, we show that 5-Lipoxygenase (5-LO) and Leukotriene B4 (LTB4) are critical for leukocyte recruitment and resistance to pulmonary A. fumigatus challenge in a fungal-strain-dependent manner. 5-LO activity was needed in radiosensitive cells for an optimal anti-fungal response and in vivo LTB4 production was at least partially dependent on myeloid-derived hypoxia inducible factor-1α. Overall, this study reveals a role for host-derived leukotriene synthesis in innate immunity to A. fumigatus.